Efficient one-pot synthesis of alpha-amino phosphonates catalyzed by bismuth nitrate pentahydrate - Bhattacharya, Asish K.; Kaur, Tanpreet (Synlett, 2007)
A simple, efficient, and environmentally benign method has been developed for the synthesis of alpha-amino phosphonates through a one-pot reaction of aldehydes with amines and diethyl phosphite in the presence of bismuth nitrate pentahydrate as a catalyst. Some of the major advantages of this protocol are: good yields, the involvement of a less-expensive and non-toxic catalyst, mild and solvent-free reaction conditions and also tolerance towards other functional groups present in the substrates. Eighteen examples are described, highlighting the substrate scope of the reaction.
Keywords: aldehydes; alkyl phosphite; alpha-amino phosphonates; amines; bismuth nitrate pentahydrate; synthetic methods

Efficient method for the synthesis of acylals from aldehydes under solvent-free conditions catalyzed by antimony trichloride - Bhattacharya, Asish K.; Mujahid, Mohammad; Natu, Arvind A. (Synthetic Communications, 2008)
A mild and efficient method has been developed for the preparation of acylals from aldehydes catalyzed by antimony trichloride under solvent-free conditions in very good to excellent yields. The easy availability, low cost, and ease of handling of the catalyst make this procedure especially attractive for large-scale synthesis.
Keywords: acetic anhydride; Acylals; aldehydes; antimony trichloride; solvent-free conditions

Efficient synthesis of benzodiazepinyl phosphonates as clostripain inhibitors via FeCl3 catalyzed four-component reaction - Bhattacharya, Asish K.; Rana, Kalpeshkumar C.; Raut, Dnyaneshwar S.; Mhaindarkar, Vaibhav P.; Khan, Mohammad Islam (Organic & Biomolecular Chemistry, 2011)
A novel one-pot route for the synthesis of benzodiazepinyl phosphonates (BDPs) has been achieved. FeCl3 efficiently catalyzed four-component condensation of diamines, acetone and phosphites in the presence of molecular sieves to furnish BDPs as novel chemical entities with good yield. The synthesized BDPs have shown significant protease inhibition activity against clostripain, a disease model for gas gangrene, suggesting that these novel chemical entities could be further explored as cysteine protease inhibitors.

Efficient synthesis of a hydroxyethylamine (HEA) isostere and its alpha-aminophosphonate and phosphoramidate derivatives as potential anti-HIV agents - Bhattacharya, Asish K.; Rana, Kalpeshkumar C.; Pannecouque, Christophe; De Clercq, Eric (Chemmedchem, 2012)
HIV protease is a promising drug target for AIDS therapy, and several potent HIV-1 protease inhibitors have been reported to date. Although existing inhibitors exhibit high selectivity, they have also been associated with severe side effects and the possible emergence of therapeutic resistance. As HIV protease cleaves the peptide bond via a tetrahedral intermediate, various transition-state models such as hydroxyethylamine (HEA) have been designed. We therefore pursued an efficient synthesis of an HEA isostere; this was performed with a novel one-pot reductiontransiminationreduction reaction sequence as a key step. a-Aminophosphonate and phosphoramidate derivatives of the HEA isostere were designed and synthesized, and all of the synthesized derivatives were assayed for their anti-HIV activities against wild-type and mutant HIV strains. Phosphoramidate derivative 15?a was found to be the most active of all synthesized compounds against the IIIB and RES056 strains. As phosphonates are known to exhibit physiological stability, good cell permeability, and other promising pharmacokinetic characteristics, our newly synthesized compounds have the potential as alternatives to existing therapeutics and diagnostics.
Keywords: a-aminophosphonates; antiviral agents; hydroxyethylamine isosteres; phosphoramidates; synthesis

Efficient bakers' yeast-catalyzed multicomponent synthesis of -aminophosphonates in one pot - Bhattacharya, Asish K.; Mujahid, Mohammad (Synthetic Communications, 2013)
Utilizing bakers' yeast (Saccharomyces cerevisiae) as a biocatalyst, synthesis of -aminophosphonates in one pot has been accomplished by the three-component reaction of an aldehyde, an amine, and diethyl phosphite in moderate to good yields under solvent-free reaction conditions. Supplemental materials are available for this article. Go to the publisher's online edition of Synthetic Communications (R) to view the free supplemental file.
Keywords: -aminophosphonates; aldehydes; amines; green chemistry; Saccharomyces cerevisiae; solvent-free conditions

Efficient synthesis of 1,5-benzodiazepines catalyzed by bismuth nitrate - Bhattacharya, Asish K.; Dange, Santoshkumar S.; Polanki, Innaiah K.; Chand, Hemender R. (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2014)
An efficient method has been developed for the synthesis of biologically active 1,5-benzodiazepines in one-pot by reacting o-phenylenediamine and ketones catalyzed by bismuth nitrate pentahydrate at room temperature or under microwave irradiation.
Keywords: 1; 5-benzodiazepines; bismuth nitrate pentahydrate; o-Phenylenediamine; synthetic methods

Enantioselective synthesis of gamma-phenyl-gamma-amino vinyl phosphonates and sulfones and their application to the synthesis of novel highly potent antimalarials - Aratikatla, Eswar K.; Kalamuddin, Md; Malhotra, Pawan; Mohmmed, Asif; Bhattacharya, Asish K. (ACS Omega, 2020)
Racemic and enantioselective syntheses of gamma-phenyl-gamma-amino vinyl phosphonates and sulfones have been achieved using Horner-Wadsworth-Emmons olefination of trityl protected alpha-phenyl-alpha-amino aldehydes with tetraethyl methylenediphosphonate and diethyl ((phenylsulfonyl)methyl)phosphonate, respectively, without any racemization. The present strategy has also been successfully applied to the synthesis of peptidyl vinyl phosphonate and peptidyl vinyl sulfone derivatives as potential cysteine protease inhibitors of Chagas disease, K11002, with 100% de. The developed synthetic protocol was further utilized to synthesize hybrid molecules consisting of artemisinin as an inhibitor of major cysteine protease falcipain-2 present in the food vacuole of the malarial parasite. The synthesized artemisinin-dipeptidyl vinyl sulfone hybrid compounds showed effective in vitro inhibition of falcipain-2 and potent parasiticidal efficacies against Plasmodium falciparum in nanomolar ranges. Overall, the developed synthetic protocol could be effectively utilized to design cysteine protease inhibitors not only as novel antimalarial compounds but also to be involved in other life-threatening diseases.